Did trade openness affect income distribution in Latin America? Evidence for the years 1980 - 2010 - Miguel Székely; Claudia Sámano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper offers a medium-term perspective for analysing the trade openness - inequality relationship in Latin America. We present three contributions. The first is that we assemble a database on income distribution indicators systematically estimated from household surveys with emphasis on within-country consistency of methodology, definitions, and coverage for the years 1980-2010. This 30-year database allows observing clearly that the increases in inequality throughout the 1980s and 1990s decades have been almost totally counteracted by the improvements during the first 10 years of the twenty-first century: 75 per cent of the deterioration in income distribution was reversed in the first decade of 2000. The second is an estimation of the association between trade openness and income distribution over the 30-year period. Our central conclusion in this regard is that greater trade openness is associated with contemporaneous increases in inequality in the region. The third is that trade openness contributed - together with other factors - to the increase in inequality during the 1980s and 1990s, but once fully implemented, it did not lead to further rises in inequality, and did not represent a permanent obstacle to improvements in income distribution triggered by other factors such as greater education levels across the population.
Keywords: F1; I3; 330; inequality; education; trade; Einkommensverteilung; Internationale Wirtschaft; Lateinamerika